Effect of body size on heavy metal contents and concentrations in green-lipped mussel Perna viridis (Linnaeus) from Malaysian coastal waters - Yap, Chee Kong; Ismail, Ahmad; Tan, Soon Guan (Universiti Putra Malaysia Press, 2009)
The concentrations of cadmium, copper, zinc and lead, in the total soft tissues of green-lipped mussel Perna viridis of a wide range of sizes (2-11 cm), were determined from a population at Pasir Panjang. The metal contents (μg per individual) and concentrations (μg per g) of cadmium, lead, copper and zinc were studied in P. viridis to find the relationships with body sizes. Smaller and younger mussels showed higher concentrations (μg per g) of Cd, Pb and Zn than the larger and older ones. The results of the present study showed that the plotting of the metal content, against dry body flesh weight on a double logarithmic basis, gave good positive straight lines; this observation is in agreement with Boyden’s formula(1977). This indicated that P. viridis showed a different physiological strategy for each metal being studied, which is related to age.